JEJAK KRATON SULTAN AGUNG (REKONSTRUKSI AWAL BERDASARKAN DATA ARKEOLOGIS DAN HISTORIS) - Alifah (Berkala Arkeologi, 2009)
Kerto, as one of the government’s centers of Mataram Islamic Kingdom within Sultan Agung era, often dismissed in historical reconstruction due to the minimity of archaeological as wall as historical data obtain from Kerto. It is often assumed that Kerto is not a center of kingdom but it is just a temporary rest house. This paper attempts to bring evidence of archaeological data and historical data of Kerto Palace to uncover the role of Kerto as a center of a kingdom, both in the political, economic social, cultural or religious.